Service quality and customer satisfaction: comparing undergraduate and graduate students perception of an HEI - Milan, Gabriel Sperandio; Eberle, Luciene; Corso, Anderson; De Toni, Deonir (Revista de Administração da UFSM, 2015)
The study aimed the main attributes and services quality dimensions identification and evaluation of an HEI (Higher Education Institution), comparing the students’ perception of a Undergraduate and Lato Sensu Graduate courses, which influence in the satisfaction levels with services rendering, its possibility to repurchase and its indication to third parties. Thus, the research was implemented in two phases, a qualitative-exploratory and another quantitative-descriptive phase, with the survey application. By means the Exploratory Factor Analysis, for the Undergraduate students, 10 services quality dimensions were identified, covered by 39 attributes. For the Lato Sensu Graduate courses students, 6 dimensions were identified, consisting of 40 attributes. By identifying and assessing these attributes and services quality dimensions from the students perspective, there is the possibility to contribute to better planning and academic and institutional performance.